Evaluating a process‐based model for use in streambank stabilization: insights on the Bank Stability and Toe Erosion Model (BSTEM). Issue 1 (15th December 2016) - Klavon, Kate; Fox, Garey; Guertault, Lucie; Langendoen, Eddy; Enlow, Holly; Miller, Ron; Khanal, Anish
Abstract: Streambank retreat is a complex cyclical process involving subaerial processes, fluvial erosion, seepage erosion, and geotechnical failures and is driven by several soil properties that themselves are temporally and spatially variable. Therefore, it can be extremely challenging to predict and model the erosion and consequent retreat of streambanks. However, modeling streambank retreat has many important applications, including the design and assessment of mitigation strategies for stream revitalization and stabilization. In order to highlight the current complexities of modeling streambank retreat and to suggest future research areas, this paper reviewed one of the most comprehensive streambank retreat models available, the Bank Stability and Toe Erosion Model (BSTEM), which has recently been integrated with several popular hydrodynamic and sediment transport models including the Hydrologic Engineering Center's River Analysis System (HEC‐RAS). The objectives of this paper were to: (i) comprehensively review studies that have utilized BSTEM and report their findings, (ii) address the limitations of the model so that it can be applied appropriately in its current form, and (iii) suggest directions of research that will help make the model a more useful tool in future applications. The paper includes an extensive overview of peer reviewed studies to guide future users of BSTEM. The review demonstrated that the model needs further testing and evaluation outside of the central United States. Also, further development is needed in terms of accounting for spatial and temporal variability in geotechnical and fluvial erodibility parameters, incorporating subaerial processes, and accounting for the influence of riparian vegetation on streambank pore‐water pressure dynamics, applied shear stress, and erodibility parameters. Copyright © 2016 John Wiley & Sons, Ltd.